Immuno-logical enhancement system by genetic vaccines. - Mohd. Lila, Mohd. Azmi; Lai, Kit Yee (2002)

(untitled)
A method is invented for enhancing humoral immune response of DNA vaccine by incorporating a viral nucleoprotein (NP) gene as part of the vaccine. The NP gene joins with a target protein gene and encodes an antigenic protein for which specific antibodies shall be produced. The 6xHis DNA sequence (ATC ATC ATC ATC ATC ATC) that encodes the 6xHis protein (also known as His protein) is incorporated either in front of the DNA sequence that encodes the NP, or between the NP and the target protein genes, or at the end of the DNA sequence that encode the target protein. To enable the insertion of any target protein gene, a multiple cloning site (MCS) is placed at the location immediately after the DNA sequence that encodes NP. The recombinant plasmid (or genetic vaccine) shall be purified and adminstered into the hos by injection or any other means. The vaccination will facilitate in vivo expression of NP-terget protein to induce or enhance antibody response against target protein concurrently with cell-mediated immune response.